Early adaptation aspects extraction in web development. (11th February 2011) - Dargham, Joumana; Aoude, Loa; Karam, Marcel
One important issue that pleases the web applications' users and draws their attention is the adaptability of the application manipulated, where web pages can change content upon user's needs and characteristics. Some approaches were developed in order to introduce adaptation into web development cycle, but they imposed some drawbacks in that they drag cross-cutting concerns into applications limiting their reusability and maintainability. Moreover, when adaptability is not considered from the early stages of development, the requirements traceability and thus the system evolvability are limited. In this paper, we propose to deal with adaptation at the early stages of development to conserve evolvability of the system. Classification of adaptation data into different categories is proposed to simplify the adaptation extraction process. This latter is implemented as a tool (AdRex) based on natural language processing techniques; it separates the adaptation features and represents them separately from the other functional and non-functional requirements to be converted into design and then implementation artefacts.